146k views
1 vote
4(2*2 + 3) - 2*2 = -(3*2 - 1) + 29

User Jiloc
by
5.2k points

2 Answers

3 votes

Answer:

24=24

Explanation:

4(4+3) - 4 = -(6-1) + 29

4 * 7 -4 = -5 + 29

24 = 24

User Fabio Barros
by
5.2k points
4 votes

Answer:

24 = 24

Explanation:

PEMDAS

The PEMDAS rule is an acronym representing the order of operations in math:

  • Parentheses
  • Exponents
  • Multiplication and Division (from left to right)
  • Addition and Subtraction (from left to right)

Solution Option 1

(Taking * as a multiplication sign)

Given equation:

4(2 × 2 + 3) - 2 × 2 = -(3 × 2 - 1) + 29

Following the order of operations, carry out the operations inside the parentheses first, starting with the multiplication:

4(4 + 3) - 2 × 2 = -(6 - 1) + 29

Carry out the addition and subtraction inside the parentheses:

4(7) - 2 × 2 = -(5) + 29

Now carry out the multiplication:

28 - 4 = -5 + 29

Finally carry out the addition and subtraction:

24 = 24

Solution Option 2

(Taking * as a "raising to the power of" sign)

Given equation:

4(2² + 3) - 2² = -(3² - 1) + 29

Following the order of operations, carry out the operations inside the parentheses first, starting with the exponents:

4(4 + 3) - 2² = -(6 - 1) + 29

Carry out the addition and subtraction inside the parentheses:

4(7) - 2² = -(5) + 29

Now carry out the exponents:

28 - 4 = -5 + 29

Finally carry out the addition and subtraction:

24 = 24

User Gartenriese
by
5.2k points